412 Sacubitril/valsartan promotes cardiac reverse remodeling and preserves renal function in a real-world heart failure and reduced ejection fraction (HFrEF) population. (17th January 2020) - Polito, M V; Rispoli, A; Vitulano, V; D"auria, F; Silverio, A; De Angelis, E; Loria, F; Citro, R; Galasso, G; Iaccarino, G; Ciccarelli, M
Abstract: Funding Acknowledgements: none Aims. To evaluate the effects of Sacubitril/Valsartan (S/V) on clinical, laboratory and echocardiographic parameters and outcomes in a real-world population with heart failure with reduced ejection fraction (HFrEF). Methods and results. Prospective study enrolling consecutive patients with HFrEF treated with S/V.The primary outcome was HF rehospitalization;secondary outcomes were all-cause death, cardiac death and the composite of cardiac death and HF rehospitalization at 12 months follow up.The clinical outcome was compared with a retrospective cohort of 90 HFrEF patients treated with standard medical therapy by using propensity score weighting. At 6 months follow-up, changes in symptoms, echocardiographic parameters, eGFR and furosemide dose were also evaluated. The study population consisted of 90 patients (66.1 ± 11.7 years). At 6 months FU, a significant improvement in NYHA class, LVEF (from 31.0% to 34.0%; p = 0.001), LVESV (from 115.0 to 101.0 mL; p = 0.033) and sPAP (from 31.0 to 25.0 mmHg; p = 0.024) was observed. Moreover, S/V did not affect negatively eGFR and was associated with a significantly lower dose of furosemide prescribed. The propensity score weighting adjusted regression analysis showed a significantly lower risk for HF rehospitalization (HR, 0.131; 95% CI, 0.034-0.503; p = 0.003) and the composite outcome (HR, 0.162; 95% CI, 0.053-0.492; p = 0.001) among patients treated with S/V as compared to the standard therapy group. Conclusions: In this real-world HFrEF population, S/V reduced HF rehospitalization and cardiac death at 1 year. Moreover, S/V improved significantly NYHA class, LVEF, LVESV and sPAP at 6 months, preserving renal function and reducing the need of furosemide.